Gyrotactic microbes' movement in a magneto-nano-polymer induced by a stretchable cylindrical surface set in a DF porous medium subject to non-linear radiation and Arrhenius kinetics - Sarkar, Soumitra; Das, Sanatan (International journal of modelling & simulation, 2025)
Because of its numerous uses in biotechnology, bioengineering, biosensors, and bioinformatics, bioconvection involving microbes and nanoparticles has attracted interest in academic circles. In this study, thermal bio-convection involving swimming microbes over a stretching cylindrical surface with wall slip embedded in a porous regime will be numerically simulated and mathematically represented by the cumulative consequences of an inclination magnetic field, non-linear heat radiation, Brownian motion, thermophoresis, Arrhenius kinetics, and stratification. The study employs the Sutterby fluid model to characterize the rheological behaviour of nano-polymeric suspension and uses the Darcy-Forchheimer (DF) model to account for porous media impedance in the transport equations. The study also employs similarity transformations to convert the set of non-linear PDFs into a collection of paired ODEs. These converted ODEs are subsequently solved by employing the numerical integration approach Runge-Kutta-Fehlberg (RKF-45) and a shooting algorithm. The effects of key physical elements on transport profiles are demonstrated using tables and figures. The simulated findings showed that nanoparticle concentration dramatically improved with growing the chemical reaction and activation energy parameters. However, it can be acknowledged that increasing the Darcy number reduces the velocity components while increasing the Forchheimer number has the opposite impact.